Pharmacological management of breathlessness in COPD: recent advances and hopes for the future. (2nd July 2016) - O'Donnell, Denis E.; Webb, Katherine A.; Harle, Ingrid; Neder, J. Alberto
ABSTRACT: Introduction: Activity-related breathlessness is often the dominant symptom in patients with chronic obstructive pulmonary disease (COPD) and usually persists despite optimal medical therapy. Currently, our inability to meaningfully alter the pathophysiology of the underlying disease means that we must focus our attention on relieving this distressing symptom so as to improve exercise tolerance and quality of life. Areas covered: The current review examines the neurobiology of breathlessness and constructs a solid physiological rationale for amelioration of this distressing symptom. We will examine the efficacy of interventions which: 1) reduce the increased central drive to breathe (opioids); 2) improve the respiratory system's ability to appropriately respond to this increased demand (bronchodilators); and 3) address the important affective dimension of breathlessness (anxiolytics). Expert commentary: Advances in our understanding of the mechanisms of activity-related breathlessness in COPD, and its measurement in the clinical domain, now set the stage for the development of effective management strategies on an individual patient basis.